PENGARUH PENERAPAN SISTEM INFORMASI RUMAH SAKIT TERHADAP KINERJA KARYAWAN BAGIAN PELAYANAN DI RUMAH SAKIT PKU MUHAMMADIYAH BANTUL - Gavinov, Ivan Tinarbudi (ALBAMA: JURNAL BISNIS ADMINISTRASI DAN MANAJEMEN, 2023)
The Information System at General Hospital PKU Muhammadiyah Bantul has supported the performance of employees in the service section which continuously uses the hospital information system. However, even though based on preliminary studies and observations, there are still problems such as control or follow-up of any part that is not continuous, data updates that are too late to do, lack of human resources who understand the information system which amounts to 3 peoples and still lack awareness of the importance from hospital information system on health service quality.The purpose of this study was to determine the influence of the application of hospital information systems on the performance of service employees in General Hospital PKU Muhammadiyah Bantul. This research method uses quantitative method with cross sectional research design and multiple linear regression test. The sample used was 77 peoples in the service section at General Hospital PKU Muhammadiyah Bantul. Measuring tool using a questionnaire. The results of the study with multiple liner regression test obtained F count 6,597 > F table 2,499 and p value 0,000 < Î± (0,05). This research show that the application of hospital information system about accuracy, timely, security, and confidentiality has influence to the performance of the health service section in General Hospital PKU Muhammadiyah Bantul with a regression coefficient of 2,229; 2,648; 2016 and 1,507. There is a influence between the application of information systems in the form of accuracy, timely, security and confidentiality on the performance of service employees in PKU Muhammadiyah Hospital Bantul.